Secondary Hyperparathyroidism Due To Hypocalcaemia and Vitamin D Deficiency in A Young Adult with Chronic Kidney Disease: A Case Report - Marsha Pareira, Francesca Melissa; Mudjanarko, Sony Wibisono (Journal of Neonatal Surgery, 2025)
Background: Secondary hyperparathyroidism (SHPT) is a common and significant complication in patients with chronic kidney disease (CKD), especially in advanced stages. It is triggered by disturbances in calcium, phosphate, and vitamin D metabolism, leading to parathyroid hyperplasia and overproduction of parathyroid hormone (PTH) [1]. This case report describes an 18-year-old female with stage V CKD, who developed SHPT associated with hypocalcaemia and vitamin D deficiency. In addition to her kidney disease, the patient had growth hormone (GH) deficiency, which complicated the clinical picture. Case Presentation: The patient, an 18-years-old high school student, presented with symptoms of fatigue, difficulty walking, and persistent lower back pain. Laboratory findings revealed severe hypocalcaemia, elevated PTH, and vitamin D deficiency. Radiological imaging confirmed the presence of bilateral parathyroid adenomas and evidence of renal osteodystrophy. Growth hormone deficiency was diagnosed based on laboratory values, which may have contributed to her worsening kidney function. Initial therapy with calcium supplementation and vitamin D analogs resulted in marked improvement in biochemical markers and symptoms. Conclusion: This case highlights the importance of early diagnosis and comprehensive management of secondary hyperparathyroidism in patients with CKD, especially in young adults. Additionally, the potential interplay between CKD and growth hormone deficiency requires further research to guide optimal treatment strategies.